Difference in tongue strength using visual feedback in healthy adults - Kim, Ji-Hoon (J Phys Ther Sci, 2017)
[Purpose] This study investigated the difference in tongue strength with and without visual feedback in healthy adults. [Subjects and Methods] A total of 30 healthy adults were recruited. We measured the strength of the anterior region of the tongue before and after applying visual feedback using the Iowa Oral Performance Instrument. [Results] The tongue strength was measured as 45.5 ± 9.3 kilopascals with visual feedback and 41.1 ± 8.6 kilopascals without visual feedback, showing a statistically significant difference. [Conclusion] Visual feedback may be an effective tool for increasing the strength of the tongue.